1993
DOI: 10.1037/1040-3590.5.3.336
|View full text |Cite
|
Sign up to set email alerts
|

The Thought Disorder Index: A reliability study.

Abstract: This article reports interrater reliability among 4 teams of raters who independently evaluated thought disorder in 20 Rorschach protocols using the Thought Disorder Index (TDI). Intraclass correlation coefficients were calculated to assess the degree of association among the 4 teams for total thought disorder scores, severity levels, and qualitative thought disorder factors. Highly acceptable agreement was obtained. Spearman rank order correlation coefficients for these same variables were significant for all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…TDI total score has been shown to have good inter-rater reliability, with correlations ranging from .80 to .93 (Coleman et al, 1993;Johnston & Holzman, 1979;Solovay et al, 1987) and an intra-class correlation (ICC) of .74 (Coleman et al, 1993 (Solovay, Shenton, & Holzman, 1987, p. 18). …”
Section: Methodsmentioning
confidence: 99%
“…TDI total score has been shown to have good inter-rater reliability, with correlations ranging from .80 to .93 (Coleman et al, 1993;Johnston & Holzman, 1979;Solovay et al, 1987) and an intra-class correlation (ICC) of .74 (Coleman et al, 1993 (Solovay, Shenton, & Holzman, 1987, p. 18). …”
Section: Methodsmentioning
confidence: 99%
“…Coleman et al (1993) found strong inter-rater reliability for TDI total scores ranging from r s = .80 to .90. Furthermore, Coleman et al (1993) showed intraclass correlations of .77, .72, and .77 for levels 0.25, 0.5, and 0.75, respectively (there were not enough responses at the 1.0 level to calculate reliability), and intraclass correlations of .58, .76, and .86 for idiosyncratic verbalizations, combinatory thinking, and irrelevant intrusions, respectively (these were the only categories for which there were enough instances to calculate reliability). Finally, it should be noted that the TDI has been shown to be unrelated to race and socioeconomic status (Haimo & Holzman, 1979;Johnston & Holzman, 1979) and use of the Rorschach in assessing thought disorder has received support even from strong critics of the Rorschach (Lillienfeld, Wood, & Garb, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Solovay, Shenton, and Holzman (1987) examined a sample of individuals with schizophrenia, bipolar disorder and healthy controls, and showed strong inter-rater reliability using the Spearman-Brown formula for two independent raters for TDI total score (r = .89), severity level (r = .79), and categories (r = .81). Coleman et al (1993) used four independent teams of raters to examine thought disorder severity in a sample of individuals with schizophrenia, schizoaffective disorder, or bipolar disorder, as well as first-degree relatives of these patients. Coleman et al (1993) found strong inter-rater reliability for TDI total scores ranging from r s = .80 to .90.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Solovay, Shenton, and Holzman (1987) examined a sample of individuals with schizophrenia, bipolar disorder and healthy controls, and showed strong inter-rater reliability using the Spearman-Brown formula for two independent raters for TDI total score (r = .89), severity level (r = .79), and categories (r = .81). Coleman et al (1993) used four independent teams of raters to examine thought disorder severity in a sample of individuals with schizophrenia, schizoaffective disorder, or bipolar disorder, as well as first-degree relatives of these patients. Coleman et al (1993) found strong inter-rater reliability for TDI total scores ranging from r s = .80 to .90.…”
Section: Thought Disorder Index (Tdi)mentioning
confidence: 99%
“…Coleman et al (1993) used four independent teams of raters to examine thought disorder severity in a sample of individuals with schizophrenia, schizoaffective disorder, or bipolar disorder, as well as first-degree relatives of these patients. Coleman et al (1993) found strong inter-rater reliability for TDI total scores ranging from r s = .80 to .90. Furthermore, Coleman et al (1993) showed intraclass correlations of .77, .72, and .77 for levels 0.25, 0.5, and 0.75, respectively (there were not enough responses at the 1.0 level to calculate reliability), and intraclass correlations of .58, .76, and .86 for idiosyncratic verbalizations, combinatory thinking, and irrelevant intrusions, respectively (these were the only categories for which there were enough instances to calculate reliability).…”
Section: Thought Disorder Index (Tdi)mentioning
confidence: 99%